A clinically silent tumour of adrenal myelolipoma: A case report - Nornazirah Azizan; Ohnmar Myint; Aye Aye Wynn; Tin Tin Thein; Firdaus Hayati; Nik Amin Sahid Nik Lah (2020)
ABSTRACT INTRODUCTION: Adrenal myelolipoma is a rare, non-functional, benign neoplasm which is constituted of mature haematopoietic elements and adipose tissues in various proportions. It is diagnosed accidentally and frequently with the widespread use of imaging modalities. PRESENTATION OF CASE: We report a 63-year-old lady with incidental findings of adrenal tumour on computed tomography (CT) scan during a routine medical check-up. She underwent tumour resection in view of a large tumour of 7 cm in size. DISCUSSION: CT scan is sensitive to diagnose adrenal myelolipoma in view of its fat-laden property and useful to monitor the tumour progress. Even previously she opted for conservative management; the decision for surgery was made in view of enlarging tumour and risk of surrounding tissue compression. CONCLUSION: With increased awareness, the detection rate of this tumour is improving, hence able to prevent the complications of a large tumour such as compression, bleeding and tumour necrosis